BENTUK GANTI KERUGIAN TERHADAP KORBAN TINDAK PIDANA PERKOSAAN DITINJAU DARI PERSPEKTIF VIKTIMOLOGI - Christiari, I Gusti Ayu; Sri Utari, A. A. (Kertha Wicara : Journal Ilmu Hukum, 2014)
The various kinds of crime is a phenomenon that occurs in the community, one of the crimes is the crime of rape. The purpose of this paper is to determine the cause of someone being victims and compensation that can be obtained by crime victims of rape. With normative method is to the statute approach will review norms to shape blur compensation of the victims. Crime victims of rape can be caused by the influence of her own. Crime victims compensation in the form of rape material and immaterial. It can be concluded, the crime of rape and its victims can not be separated, which usually be a crime victims of rape is a woman. These compensation may be filed by crime victims of rape by the Agency. Compensation which comes first is immaterial compensation in the form of psycho - social rehabilitation.
Keywords: Compensation, Victim, Rape, Victimology